Earth Science Education 5. Effective Industry Outreach. Two Leading Examples from the Mineral Industry - Dillon, Patricia; Lipkewich, Maureen (Geoscience Canada, 2002)
In an effort to provide information to the public through educators, resource-based industries have commonly produced glossy literature and graphics packages that were not necessarily appropriate for the school curriculum, and therefore remained under used. A major change in approach,that of engaging teachers to design and develop the outreach resources, was successfully implemented by the Mining Association of British Columbia in 1991. Following on this success the Prospectors and Developers Association of Canada developed a similar program in 1994. Since their inception these programs have collectively distributed their resources to more than 10,000 teachers, who have in turn used them in teaching hundreds of thousands of students. It is hoped that this review of these programs will encourage other industry groups to develop similar approaches to outreach resource material.